2004
DOI: 10.1590/s0100-879x2004000400001
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulation of the hypothalamo-neurohypophyseal system

Abstract: Nitric oxide (NO), a free radical gas produced endogenously from the amino acid L-arginine by NO synthase (NOS), has important functions in modulating vasopressin and oxytocin secretion from the hypothalamo-neurohypophyseal system. NO production is stimulated during increased functional activity of magnocellular neurons, in parallel with plastic changes of the supraoptic nucleus (SON) and paraventricular nucleus. Electrophysiological data recorded from the SON of hypothalamic slices indicate that NO inhibits f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
1
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 63 publications
7
48
1
6
Order By: Relevance
“…At the beginning of the test period, IRL 1620 (N-succinyl-[Glu 9 ,Ala 11,15 ]-endothelin-1 fragment 8-21; Sigma RBI), a selective ETB receptor agonist, was added to the hypothalamic side of the barrier. Concentration of IRL 1620 ranged from 0.1 pM to 10 nM.…”
Section: Compartmentalized Protocolsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the beginning of the test period, IRL 1620 (N-succinyl-[Glu 9 ,Ala 11,15 ]-endothelin-1 fragment 8-21; Sigma RBI), a selective ETB receptor agonist, was added to the hypothalamic side of the barrier. Concentration of IRL 1620 ranged from 0.1 pM to 10 nM.…”
Section: Compartmentalized Protocolsmentioning
confidence: 99%
“…Recent studies indicate that nitric oxide generated by neural-astroglial sources modifies ET signaling within the central nervous system (19,27,42). Immunohistochemical and in situ hybridization studies have demonstrated nitric oxide synthase (NOS), citrulline, and NADPH-diaphorase activity within the hypothalamo-neurohypophyseal system (HNS; 11,39,42). Osmotic or hypovolemic stimuli that increase activity of magnocellular neurons are associated with enhanced NADPH-diaphorase activity in this region (21,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…b-DG, a1-Syn, and utrophins) in the SON and the PVN of the Dp71-null hypothalamus. We also analyzed nNOS expression, because this protein potentially interacts with the DAPC and because it represents an index of osmoregulatory axis activation (Kadekaro 2004). Indeed, in the hypothalamoneurohypophysis complex, NO is an important modulator of vasopressin synthesis and secretion (Yuan et al 2006, Raison et al 2011, St-Louis et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the hypothalamoneurohypophysis complex, NO is an important modulator of vasopressin synthesis and secretion (Yuan et al 2006, Raison et al 2011, St-Louis et al 2012. nNOS and NADPH diaphorase, the histochemical marker of NOS activity, are both present in magnocellular neurons (Grange-Messent et al 2004, Kadekaro 2004, Maolood et al 2007. Their expression levels and activity increase when magnocellular neuron activity increases in response to osmotic stimulation, dehydration, or hypovolemia (Kadowaki et al 1994, Villar et al 1994, Ueta et al 1995.…”
Section: Introductionmentioning
confidence: 99%